Regulating Complexity in Financial Markets - Steven L. Schwarcz (Washington University Law Review, 2009)
As the financial crisis has tragically illustrated, the complexities of modern financial markets and investment securities can trigger systemic market failures. Addressing these complexities, this Article maintains, is perhaps the greatest financial-market challenge of the future. The Article first examines and explains the nature of these complexities. It then analyzes the regulatory and other steps that should be considered to reduce the potential for failure. Because complex financial markets resemble complex engineering systems, and failures in those markets have characteristics of failures in those systems, the Article’s analysis draws on chaos theory and other approaches used to analyze complex engineering systems.
Keywords: Chaotic behavior in systems; Financial crises; Capital market -- Law & legislation; Risk management in business